2014
DOI: 10.4314/ijbcs.v8i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Morphological alteration of seminiferous tubules of testes of Wistar rat offspring exposed to alcohol during pregnancy and/or lactation

Abstract: This paper presents the effects of alcohol on the morphology of seminiferous tubules of testes of Wistar rat offspring exposed to alcohol during pregnancy and/or lactation. Seventy five adult female Wistar rats divided into 3 groups of 25 each and their offsprings were used. The offspring of group 1 served as control, those of group 2 were exposed to 2 g/kg body weight of 30% ethanol (v / v) during pregnancy and lactation (APL) while those of group 3 were exposed to the same dose of ethanol during lactation on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…In the present study, we observed reductions of the gonadosomatic index and the diameter of seminiferous tubules. These results are consistent with findings in rat offspring that were exposed to ethanol during pregnancy or lactation (Onu, Oke, Ozegbe, & Oyewale, 2014). Interestingly, these morphological alterations were not accompanied by alterations of testosterone levels, which could be attributable to the increase in the number of Leydig cells in ethanol mice.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we observed reductions of the gonadosomatic index and the diameter of seminiferous tubules. These results are consistent with findings in rat offspring that were exposed to ethanol during pregnancy or lactation (Onu, Oke, Ozegbe, & Oyewale, 2014). Interestingly, these morphological alterations were not accompanied by alterations of testosterone levels, which could be attributable to the increase in the number of Leydig cells in ethanol mice.…”
Section: Discussionsupporting
confidence: 92%
“…Alcohol consumption during pregnancy is associated with fetal alcohol syndrome (FAS) [1]. FAS is characterized by restricted fetal growth and dysfunction of the nervous system [2][3][4]. The consequence of ethanol present in the prenatal environment is associated with long-term consequences such as enduring growth retardation [5].…”
Section: Introductionmentioning
confidence: 99%